Identifying Type 2 Diabetic Brains by Investigating Disease-Related Structural Changes in Magnetic Resonance Imaging - Chen, Yuna; Pan, Yongsheng; Kang, Shangyu; Lu, Junshen; Tan, Xin; Liang, Yi; Lyu, Wenjiao; Li, Yifan; Huang, Haoming; Qin, Chunhong; Zhu, Zhangzhi; Li, Saimei; et al. (Frontiers in Neuroscience, 2021)
Diabetes with high blood glucose levels may damage the brain nerves and thus increase the risk of dementia. Previous studies have shown that dementia can be reflected in altered brain structure, facilitating computer-aided diagnosis of brain diseases based on structural magnetic resonance imaging (MRI). However, type 2 diabetes mellitus (T2DM)-mediated changes in the brain structures have not yet been studied, and only a few studies have focused on the use of brain MRI for automated diagnosis of T2DM. Hence, identifying MRI biomarkers is essential to evaluate the association between changes in brain structure and T2DM as well as cognitive impairment (CI). The present study aims to investigate four methods to extract features from MRI, characterize imaging biomarkers, as well as identify subjects with T2DM and CI.